One-pot synthesis of ultrastable pentanuclear alkylzinc complexes. Issue 8 (3rd February 2017) - Bunzen, Hana; Grzywa, Maciej; Kalytta-Mewes, Andreas; Volkmer, Dirk
Abstract : The first ever reported organometallic compounds featuring a Kuratowski-type bond topology were found to be unexpectedly chemically and thermally stable. Abstract : Two organometallic pentanuclear zinc complexes, namely [Zn5 Et4 (Me2 bta)6 ] and [Zn5 Me4 (Me2 bta)6 ], containing tridentate N-donor ligands (5, 6-dimethylbenzotriazolate, Me2 bta) were prepared by a one-pot synthesis. These compounds represent the first examples of organometallic complexes featuring a Kuratowski-type bond topology. Zinc ions were introduced as organometallic precursors (either diethylzinc or dimethylzinc was used), which upon mixing with the ligand yielded the desired complexes spontaneously. The organometallic complexes were characterized by a range of analytical techniques including NMR- and FT-IR spectroscopy, mass spectrometry, and elemental analysis. In addition, the structure of [Zn5 Et4 (Me2 bta)6 ] could be solved by single-crystal X-ray analysis. The thermal and chemical stability of the complexes was studied by TGA, VT-XRPD and DRIFT, in addition to NMR and mass spectrometric investigations. The compounds were found to be unexpectedly stable under various conditions and to lack any reactivity with electrophilic reactants such as aldehydes, which commonly react easily with organozinc compounds. However, the basic alkyl groups could be reacted with strongly acidic compounds such as trifluoroacetic acid.